Myristoylated alanine-rich C kinase substrate phosphorylation is involved in thrombin-induced serotonin release from platelets - Elzagallaai, A. (2001)
Stimulation of platelets by thrombin induces protein kinase C (PKC) activation, phosphorylation of pleckstrin, aggregation and serotonin release. Here, we demonstrate that, in human platelets, thrombin stimulation also induced phosphorylation of the myristoylated alanine-rich C Kinase substrate (MARCKS) and serotonine release in intact and digitonin-permeabilized platelets. MARKS is known to bind actin and cross-link actin filaments, and this is inhibited by PKC-evoqued MARKS phosphorylation. MARKS phosphorylation and serotonin release in response to increasing concentration of thrombin have a similar EC 50 and time course and, in permeabilized platelets, peptide MPSD, with an amino sequence corresponding to the phosphorylation site domain of MARKS, bloked both responses. However, pleckstrin and myosin light chain phosphorylations were not modified. Ala-MPSD, in which the four serine residues of MPSD were substituted by alanines was ineffective. The results suggest a role for MARKS in platelet secretion. The fact that pleckstrin phosphorylation has different time course and was not modified in the presence of MPSD when MARCKS phosphorylation and serotonine release were inhibited would suggest either that pleckstrin phosphorylation is unrelated to secretion or that it might only be involved upstream in the events leading to secretion.